Acronym Usage in Groups: The Relationship of Socialization and Identification - Dara K Carney-Nedelman (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2020)
This study analyzed the relationship between knowledge of acronym meaning and group member’s socialization and identification. It examined the understudied relationship between knowledge of acronym meaning for group members and their socialization and identification in the group. Research has concluded that when assimilated into a group the group members contribute more, and overall have greater satisfaction (Riddle, Anderson, & Martin, 2000). This assimilation can be separated into two variables, socialization and identification of group members. Research on the relationship for knowledge of acronym meaning and assimilation has been understudied; therefore, this project explored how the terms we use in groups impacts our connection within the group.
Keywords: Acronym; Group Communication; Socialization; Identification; language